The quality of non-financial information in the perspective of data disclosure - Adamczyk, Jadwiga (Jakość informacji niefinansowych w perspektywie jawności danych, 2019)
Information is a source of knowledge in enterprise management, therefore its importance increases in today’s competitive environment. High-quality and timely information reduces uncertainty and risk of decision-making, hence the great interest of stakeholders in access to information. The purpose of the article is to interpret the concept of the quality, as it relates to non-financial information, and to assess the quality of the information in terms of enterprise data disclosure. The object of research is the quality of non-financial information disclosed in corporate social reports, which depends on many factors, e.g. the choice of reporting standard and the type of business. The research shows that GRI Standards covers the broadest and most detailed range of non-financial information. Assessment of the reports demonstrates that the quality of non-financial information is also affected by the application of additional industry standards, which take into account the specificity of the enterprise
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 10, s. 147-160
Keywords: non-financial information; quality; transparency; enterprise; reporting; informacje niefinansowe; jakość; ujawnianie; przedsiębiorstwo; raportowanie